Neurobiological mechanisms of mood disorders: Stress vulnerability and resilience - Marcolongo-Pereira, Clairton; Castro, Fernanda Cristina de Abreu Quintela; Barcelos, Rafael Mazioli; Chiepe, Kelly Cristina Mota Braga; Rossoni Junior, Joamyr Victor; Ambrosio, Roberta Passamani; Chiarelli-Neto, Orlando; Pesarico, Ana Paula (Frontiers in Behavioral Neuroscience, 2022)
Stress is an important factor in the development of several human pathologies. The response of rodents and humans to stress depends on many factors; some people and rodents develop stress-related mood disorders, such as depression and anxiety in humans, depression-like and anxiety-like behavior in mice and rats, while others report no new psychological symptoms in response to chronic or acute stress, and are considered susceptible and resilient to stress, respectively. Resilience is defined as the ability to thrive in the face of adversity and is a learned process that can help protect against occupational stressors and mental illnesses. There is growing interest in the underlying mechanisms involved in resilience and vulnerability to depression caused by stress, and some studies have demonstrated that individual variability in the way animals and humans respond to stress depends on several mechanisms, such as oxidative stress, neuronal plasticity, immunology and genetic factors, among others not discussed in this review, this review provides a general overview about this mechanism.